Hubungan Status Gizi dengan Gangguan Mestruasi Pada Mahasiswa Akbid La Tansa Mashiro Rangkasbitung Tahun 2022 - Rita Ariesta (Akademi Kebidanan La Tansa Mashiro, 2022)
Dysmenorrhea is the pain felt by a woman when she is having menstruation divided into primary and secondary dysmenorrhea. Primary dysmenorrhea is usually associated with uterine muscle contraction and release of prostaglandins resulting in an increase in prostaglandins, and almost always first occurs in women aged 20 years or even younger after their ovulatory cycles become fixed. Management of primary dysmenorrhea Non-pharmacological therapy that can be done as an effort to treat dysmenorrhea without using chemical drugs, for example using emphasis on certain points. This type of research method uses case control with a population of 75 female students. The sample in this study uses the total population. The independent variables in this study were nutritional status, independent solutions, menstrual cycle, duration of menstruation, age of first menarche, while the dependent variable was dysmonorhoe. Bivariate analysis found that the nutritional status variable (P = 0.064) and the independent solution variable (P 0.00) had a relationship with the incidence of dysmenorrhea. Providing counseling about the factors that cause primary dysmenorrhea and their treatment needs to be done regularly so that prevention and treatment choices by taking drugs can be reduced.